Local History of Jakarta and MulticulturalAttitude (Historical Local Study of Betawi Ethnic) - Suswandari Suswandari (STKIP Singkawang, 2017)
This is a literature review about local history of Jakarta and multicultural attitude. In the context of local history of Jakarta, ethnic Betawi as ethnic origin Jakarta is formed from the process of inter-ethnic assimilation imported by the Dutch colonial government in its political and economic interests. In its development, the Betawi ethnic group continued to strengthen and succeeded in establishing their own distinctive identity as well as disturbing with other ethnic groups in Indonesia, although in their present development their existence is decreasing due to development interest which is not able to open wide room for Betawi ethnicity itself because various causes. The Betawi ethnic group has a strong identity concerning Betawi cultural heritage such as strong religious soul, respect for diversity, friendly, homoris, helpful, open, tolerant to differences and so on. As a part of Jakarta's local history, ethnic Betawi history can be explored as a source of inspiration and a source of awareness in instilling multicultural souls in Jakarta, as a metropolitan city with increasingly diverse ethnicity towards social life within the framework of peace and harmony.